Capital-account and counter-cyclical prudential regulations in developing countries - José Antonio Ocampo (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
This paper explores the complementary use of two instruments to manage capital-account volatility in developing countries: capital-account regulations and counter-cyclical prudential regulation of domestic financial intermediaries. Capitalaccount regulations can provide useful instruments in terms of both improving debt profiles and facilitating the adoption of (possibly temporary) counter-cyclical macroeconomic policies. Prudential regulation and supervision should take into account not only the microeconomic risks, but also the macroeconomic risks associated with boom-bust cycles. It should thus introduce counter-cyclical elements into prudential regulation and supervision, together with strict rules to prevent currency mismatches and reduce maturity mismatches. These instruments should be seen as a complement to counter-cyclical macroeconomic policies and, certainly, neither of them can nullify the risks that pro-cyclical macroeconomic policies may generate. – cycles ; capital flows ; prudential regulation ; counter-cyclical policies
Keywords: E32; F32; F41; O11; 330; Kapitalbilanz; Kapitalverkehrspolitik; Finanzintermediär; Regulierung; Entwicklungsländer